LsNAC46 regulates heat-resistance and growth in lettuce (Lactuca sativa L.) - Yang, Tao; He, Shu-ping; Huo, Guo-tao; Tian, Ming-lu; Du, Li; Yang, Xiao; Xu, Heng; Ge, Guo-jun; Zhao, Hong-yang; Luo, Li-jun; Wei, Shi-wei (Frontiers in Plant Science, 2025)
Lettuce prefers a cold and cool climate, and high temperatures can lead to many problems such as tip burn that decrease yield and quality. NAC (NAM, ATAF1/2, and CUC2) proteins are important regulatory factors in abiotic stress responses. In our previous transcriptomic analysis, we identified that LsNAC46 is involved in the response to heat stress in lettuce. This study reports that LsNAC46 (LOC111911762), a member of the NAC transcription factor family, has transcriptional activation activity, and regulates heat tolerance, growth, and development in lettuce. Tissue expression analysis showed the highest expression levels of LsNAC46 in lettuce achene. Compared with wild-type (WT) plants, LsNAC46-overexpressing lines had a higher heat damage index and lower survival rate when exposed to high temperature, accompanied by reduced accumulation of total protein (TP), proline (PRO), and phenylalanine ammonia-lyase (PAL), as well as a lower Fv/Fm, indicating that LsNAC46 negatively regulates heat tolerance in lettuce. In addition, the plant width, leaf length, and fresh weight were significantly lower, but the achene weight was significantly higher in LsNAC46-overexpressing plants. This study indicates that LsNAC46 may regulate heat stress responses by regulating intracellular enzyme activity, osmotic pressure, photosynthetic capacity, and synthesis of secondary metabolites. This knowledge may enable the characterization of LsNAC46 in the response to heat stress and regulation of plant stress responses or achene weight.